Effects of bone-conducted music on swimming performance - Tate, A. R.; Gennings, C.; Hoffmann, R. A.; Strittmatter, A. P.; Retchin, S. M. (The Journal of Strength and Conditioning Research, 2012)
Music has been shown to be a useful adjunct for many forms of exercise and has been observed to improve athletic performance in some settings. Nonetheless, because of the limited availability of practical applications of sound conduction in water, there are few studies of the effects of music on swimming athletes. The SwiMP3 is a novel device that uses bone conduction as a method to circumvent the obstacles to transmitting high fidelity sound in an aquatic environment. Thus, we studied the influence of music on swimming performance and enjoyment using the SwiMP3. Twenty-four competitive swimmers participated in a randomized crossover design study in which they completed timed swimming trials with and without the use of music delivered via bone conduction with the SwiMP3. Each participant swam four 50-m trials and one 800-m trial and then completed a physical enjoyment survey. Statistically significant improvements in swimming performance times were found in both the 50-m (0.32 seconds; p = 0.013) and 800-m (6.5 seconds; p = 0.031) trials with music using the SwiMP3. There was no significant improvement in physical enjoyment with the device as measured by a validated assessment tool. Bone-conducted music appears to have a salutary influence on swimming performance in a practice environment among competitive adult swimmers.